Simultaneous strain measurements of knee ligaments - Ng, Ivon Soon Wei (2016)
Ligaments are essential to motions, particularly forward, backward and sideways, and injuries to ligaments are commonly found among athletes due to adverse combinations of forces and torques. The objectives of this study are: firstly, to design and modify an existing custom-designed knee fixture which allows multiple degrees of freedom of the knee, and secondly, to assess the strain responses of all ligaments simultaneously under various loading conditions. Computer-aided design software, Solidworks, was used to simulate the new design and fabrication was outsourced. Experiments were conducted on cadaveric knee. DVRT (Differential Variable Reluctance Transducer) with a linear range of ±3 mm was calibrated and implanted into the ligaments by its barbed prongs. Two series of tests were performed on the cadaver: (1) Anterior and posterior directed shear load at various flexion angles (2) internal and external tibial torque at full extension. The strain values produced during anterior loading were greatest at a flexion angle of 30°, with the exception of medial collateral ligament (MCL) peaking at 60°. For posterior loading, it did not exhibit any consistent trend. During internal and external rotation, due to the shortcoming of both the fixture and the knee being osteoporotic, strain responses were collected only at full extension. Anterior cruciate ligament (ACL) and posterior cruciate ligament (PCL) was concluded as the primary stabilizer for anterior and posterior tibial translation due to the greater strain values produced as compared to the collateral ligaments. PCL is inferred to be the primary stabilizer during external rotation while ACL and lateral collateral ligament (LCL) are the secondary stabilizer due to negative strain exhibited. PCL and MCL exhibited positive strain, leading to the hypothesis that they are the primary stabilizer to internal rotation while LCL and ACL are the secondary stabilizer. Future work will be required to obtain the strain responses of internal-external rotation at other flexion angles to obtain a consistency in the results. These data collected could have important clinical ramifications during recovery processes and also allow researchers to focus on the significant loading conditions and record the responses of the ligaments.